Emerging Applications of 3D Printing in Biomanufacturing. Issue 11 (November 2021) - Gao, Hao; Zhang, Wenming; Yu, Ziyi; Xin, Fengxue; Jiang, Min
Abstract : The combination of 3D printing and synthetic biology is a sustainable strategy to fabricate biological objects and systems that behave in a preprogrammed manner. Many microorganisms have been genetically engineered as cell factories for the biosynthesis of chemicals using fermentation, and 3D printing of living materials using these cells could lead to a new paradigm for biomanufacturing.